(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This paper explores the semantic and cognitive classification of antonyms, antinomy, and contrast in Italian and Uzbek. Antonymy, as a universal linguistic phenomenon, reflects how different culture’s structure oppositional meanings. Drawing on theories from lexical semantics and cognitive linguistics, the study compares how Italian and Uzbek encode gradable, complementary, and relational oppositions. Antinomy and contrast are examined as broader conceptual processes revealing paradox and difference in thought and discourse. Using descriptive and comparative analysis based on dictionary and corpus data, the study shows that while antonymic patterns are universal, their cognitive and cultural interpretations vary, reflecting distinct linguistic worldviews.